Wages Boards in Australia: I. Victoria - Hammond, M. B. (Quarterly Journal of Economics, 1914)
Introduction: methods of wage regulation, 98. — 1. The anti-sweating movement in Victoria, 101. — 2. Origin and introduction of wages boards, 107. — Parliamentary history of the minimum wage bill, 110. — Main features of the act of 1896, 120. — 3. Extension of the system and its struggle for existence, 122. — Work of the first boards, 123. — Act of 1900, 126. — Crisis of 1902, 131. — Report of the Royal Commission in 1903, 139. — The system made permanent, 143. — 4. Growing popularity of the boards, 144.